Perkawinan Endogamy Bagi Syarifah Perspektif Sosiologis dan Maqashid Syari’ah (Study Kasus: Adat Perkawinan Endogamy di Kampung Arab Kelurahan Kademangan Bondowoso) - Fahmi Ridlol Uyun (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2018)
This article demonstrates that the notions of superiority and social power within the Alwi and Ba‘alawi communities have led to a distortion of the principles of Islamic law. This is reflected in the long-standing practice of endogamous marriage within these groups. In essence, such forms of marriage are not inherently related to Islamic legal teachings, but are instead justified by the claim of preserving the lineage of the Prophet Muhammad (peace be upon him). Endogamous marriage among Syarifah is believed to be the only legitimate means of safeguarding the Prophet’s lineage; therefore, Syarifah bear a particular social and moral responsibility to continue this practice to the present day. This thesis shows that the practice of endogamous marriage among Syarifah in Kampung Arab, Kademangan Subdistrict, represents an implementation of obedience to religious systems and values. This study employs a qualitative research design, in which the researcher examines group culture in its natural setting. The primary data consist of observations and interviews, while secondary data are derived from relevant literature. The analytical approach used in this study is the sociology of law.